Risk Factors For Tinea Imbricata In Keerom Regency, Papua, Indonesia - Watopa, Sonia Ridanti; Hidayati, Afif Nurul; Arthur Pohan Kawilarang (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Tinea imbricata is a chronic superficial fungal infection caused by Trichophyton concentricum, which is endemic in the tropics. The prevalence of this disease in endemic areas is estimated to be around 9% - 18% of the population. Keerom Regency, Papua, has one of the highest cases of Tinea imbricata and continues to be a major public health problem. Understanding the associated risk factors is critical for effective control. Purpose: This study aimed to analyze the risk factors for the incidence of Tinea imbricata in Keerom Regency, Papua. Methods: This study was an observational analytic study using case control design. Sampling was done by concecutive sampling, the ratio of the number of cases and controls was set at 1:1 (31 cases and 31 controls) so that the total sample size was 62 people. Result: The results of the study with bivariate analysis showed a significant value of risk factors for residential density (p<0.05), risk factors for contact history (p<0.05), the habit of using shared towels / clothes (p<0.05), and family history (p<0.05). Multivariate analysis showed that contact history and family history were the factors most associated with the incidence of Tinea imbricata. Conclusion: This study shows that there is a relationship between residential density, the habit of wearing towels / clothes with patients, contact history and family history and the most related factors are direct contact and family history.